2015
DOI: 10.1039/c5ra13417j
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of alcoholic liver disease: a clinical discovery study

Abstract: Metabolomics is a powerful technology which shows great potential in biomarker discovery. A total of three urinary differential metabolites were identified, and more important, these biomarkers may be sensitive to early diagnosis of ALD disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…30 Currently, the application of metabolomics to urine samples has been successful in nding potential biomarkers for diseases. [35][36][37][38][39] Our ndings have dened a panel of molecules whose levels are altered in the urine of RA patients. The urine biomarkers identied in this study exhibited satisfactory diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…30 Currently, the application of metabolomics to urine samples has been successful in nding potential biomarkers for diseases. [35][36][37][38][39] Our ndings have dened a panel of molecules whose levels are altered in the urine of RA patients. The urine biomarkers identied in this study exhibited satisfactory diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids metabolism makes metabolomics a more promising way to explore these types of diseases as the core issues in CVD. Application of metabolomics in clinical research has provided the chance to obtain new insights into metabolic change and mechanism [62][63][64]. A large amount of information bringing about by metabolomics indicated that these approaches will open a new perspective on disease processes and eventually transit from theory to clinical applications [65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…The highthroughput metabolomics can provide the tool for further investigation of the metabolic mechanism. [20][21][22][23][24][25][26][27][28][29][30][31] Therefore, we examined the long-term effects of alkalinity stress on the CC. The metabolic proles are studied by top-down thermometric analysis.…”
Section: Discussionmentioning
confidence: 99%